Characterisation of wastes collected from beaches, coastlines, marine surface cleaning processes and ships: A case study of Istanbul - Bilgili, Mehmet Sinan; Adar, Elanur; Yildiz, Senot; Sezer, Kadir (SAGE PUBLICATIONS LTD, 2019)
Marine waste management is crucial for Istanbul because of the significant location for intercontinental transition, international trade, tourism, industry and shipping. This study is the first one realised in Turkey for the detailed characterisation of marine waste. The amount and characteristics of solid wastes originating from beaches, coastlines, sea surface cleaning processes and ships (both cargo and cruise ships) were determined. It was observed that marine wastes includes a significant amount of recyclable materials. Although, it was ascertained that the amount and composition of waste differs according to the collecting sources, the majority of wastes are composed of different types of plastics. The average calorific value of marine waste was determined as 2500kcalkg(-1), which is higher than that of mixed municipal solid waste. There is a lack of studies on the pathways of disposal alternatives of marine waste after collection. As landfilling is the common pathway for disposal after collecting, it is clear that recycle/reuse and energy recovery options are possible for marine waste.
Keywords: Marine waste; recyclables; plastics; combustible waste; calorific value; SPATIAL-DISTRIBUTION; LITTER COMPOSITION; PLASTIC DEBRIS; ABUNDANCE; POLLUTION; ENVIRONMENT; SHORES; Engineering; Environmental Sciences & Ecology